Systematics molecular investigation of Palo fish (Betta sp.) in the Harau Valley, West Sumatra using the COI gene - UMMI KURNIA PUTRI; DEWI IMELDA ROESMA; DJONG HON TJONG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Putri UK, Roesma DI, Tjong DH. 2025. Systematics molecular investigation of Palo fish (Betta sp.) in the Harau Valley, West Sumatra using the COI gene. Biodiversitas 26: 698-705. Palo fish (Betta sp.) is a local ornamental fish in the Harau Valley, Lima Puluh Kota, West Sumatra, Indonesia, which was suspected to be a new species from the Betta of the Pugnax group based on the Cytochrome b gene. Molecular investigations using more reliable genes were needed to validate the taxonomic status of Palo fish and determine the phylogenetic relationship with other Betta species. The cytochrome oxidase I (COI) gene has been recognized for identification at the species level. Liver tissue samples were taken from eight Palo fish individuals from four Rangkak Hill tributaries in Harau Valley. Eight Palo fish and 44 comparison sequences were analyzed using the Aliview, IQ Tree, and MEGA VII programs. The 641 bp COI gene sequences analysis showed that Palo fish from four tributaries in Harau Valley had 100% nucleotide base similarity (identical), which shared the same haplotype. Palo fish have a close relationship with Betta stigmosa and have the least genetic distance to Betta cf. apollon (2.6%), followed by Betta ferox (3.1%) and Betta apollon (3.7%). The genetic distance values show the differences at the subspecies level within the same species. Palo fish from Harau Valley confirmed as Betta cf. stigmosa. Comprehensive studies on Betta species need to be carried out to complete the systematics of the Betta group.